2022
DOI: 10.1155/2022/8513812
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Ex Vivo Heart Perfusion with Mesenchymal Stem Cell-Derived Conditioned Medium Improves Myocardial Tissue Protection in Rat Donation after Circulatory Death Hearts

Abstract: Objective. Adopting hearts from donation after circulatory death (DCD) is a promising approach to enlarge the donor pool. Nevertheless, DCD hearts experience severe warm ischemia/reperfusion (I/R) injury. Recent studies have demonstrated that conditioned medium (CM) derived from bone marrow mesenchymal stem cells (BMSCs) has the potential of reducing organ I/R injury. Therefore, we investigated whether DCD heart preservation with normothermic ex vivo heart perfusion (EVHP) and BMSCs-CM treatment could alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…Machine perfusion provides a unique platform for selective direct injection of these MSCs directly into donor organs, overcoming homing, trafficking, and safety issues [10,20]. Recent studies by Zeng et al [28] have shown that normothermic ex vivo heart perfusion combined with bone marrow MSCs derived conditioned medium therapy can attenuate myocardial IRI for DCD heart by reducing levels of oxidative stress, inflammatory response, and apoptosis [28]. IRI is often accompanied by local or systemic inflammatory responses called "aseptic inflammation" or "damagerelated pattern molecules (DAMPs)" to distinguish them from the inflammatory response to infection.…”
Section: Mscs and Msc-evs In Irimentioning
confidence: 99%
“…Machine perfusion provides a unique platform for selective direct injection of these MSCs directly into donor organs, overcoming homing, trafficking, and safety issues [10,20]. Recent studies by Zeng et al [28] have shown that normothermic ex vivo heart perfusion combined with bone marrow MSCs derived conditioned medium therapy can attenuate myocardial IRI for DCD heart by reducing levels of oxidative stress, inflammatory response, and apoptosis [28]. IRI is often accompanied by local or systemic inflammatory responses called "aseptic inflammation" or "damagerelated pattern molecules (DAMPs)" to distinguish them from the inflammatory response to infection.…”
Section: Mscs and Msc-evs In Irimentioning
confidence: 99%
“…Багатогранний позитивний ефект МСК пов'язують із патотропним хомінгом [97], явищем нейрогенного транс диференціювання [90,[97][98][99], зокрема в нейролемоцити [100][101][102], здатністю до злиття з клітинами реципієнта [103], мікровезикулярним [104][105][106][107][108], факторним [97,[100][101][102] чи контактним [97,105] впливом. Крім того, трансплантовані МСК мають імуносупресивну і, ймовірно, локальну протизапальну дію [109][110][111][112].…”
Section: мезенхімальні стовбурові клітини при лікуванні травми перифе...unclassified